High CD200 expression is associated with poor prognosis in cytogenetically normal acute myeloid leukemia, even in FlT3-ITD-/NPM1+ patients. (July 2017) - Tiribelli, Mario; Raspadori, Donatella; Geromin, Antonella; Cavallin, Margherita; Sirianni, Santina; Simeone, Erica; Bocchia, Monica; Fanin, Renato; Damiani, Daniela
Highlights: CD200 over-expression is associated with poor prognosis in AML. In CN AML, CD200 correlated with lower rates of CR and shorter DFS and OS. Cases with high CD200 expression displayed worse outcomes. CD200 overexpression is associated with poor prognosis also in FLT3-/NPM1+ CN AML. Abstract: Overexpression of CD200, a trans-membrane protein belonging to the immunoglobulin superfamily, has been associated with poor prognosis in patients with acute myeloid leukemia (AML). As few data are available in the subset of cytogenetically-normal (CN) AML, we retrospectively evaluated the correlations between CD200 expression and response to therapy in a series of 139 adults with CN-AML. CD200 was expressed in 67/139 (48%) cases; 18 of them (28%) expressed CD200 at high intensity. No differences in CD200 expression rate were observed according to age, WBC count, type of leukemia, FLT3 or NMP1 mutation, and CD56 expression. A higher incidence of CD200 expression was observed in CD34+ cases (P < 0.0001) and in BCL2+ patients (P = 0.04). Complete remission (CR) was evaluable achieved in 98 patients (70%): 56/71 (79%) in CD200- and 47/67 (63%) in CD200+ patients (P = 0.03), with a lower CR rate in patients with high CD200 intensity (9/18, 50%). CD200 expression had a negative impact on long-term outcome. CD200 expression, per se, did not impact on disease-free survival (DFS), but cases with high CD200 expression had a lower 3-year DFS compared to CD200-negative and low-expressing ones (0% vs 65% vs 68%, P = 0.019). Three-year overall survival (OS) was 51% in CD200- and 27% in CD200+ patients (P = 0.01), with a significant difference among cases with low or high CD200 expression (35% vs 0%, P = 0.001). CD200 high expression defined a group with very poor DFS and OS also among the 37 FLT3-/NPM1+: 3-year DFS and OS were 88% and 60% in CD200-, 50% and 32% in CD200 low and 0% and 0% in CD200 high patients, respectively (P = 0.01 for DFS and P = 0.05 for OS). Our data suggest a negative impact of CD200 expression in CN-AML, with a further worsening in high-expressing cases, also in the subset of FLT3-/NPM1+ patients.